Solid organ transplant patient management undergoing oral surgery: a review of literature - Carlos Manuel Cobo-Vázquez; Luis Sánchez-Labrador; David Reininger Dueñas; Luis Miguel Sáez-Alcaide; Isabel Leco-Berrocal; Cristina Meniz-García (Journal of Stomatology)
A relationship between various specialties and adverse effects of post-transplant treatments gives rise to a permanent search for ways to reduce these complications. Aim of the study was to investigate the guidelines for the management of solid organ transplant patients after oral surgery treatment, considering medication employed. A literature review of scientific articles was carried out with systematic search. Terms used were “Oral Surgery” AND “Solid Organ Transplanted Patient” OR “Organ Transplanted”. Medline, Web of Science, and Scopus databases were explored, with no time restriction and in Spanish and English languages, complemented by a manual search. A total of 162 titles were retrieved. Out of these, six underwent full data extraction and were included in analysis. Data of 784 patients, with age ranging from 18 to 80 years, and a history of liver, heart, kidney, or pancreas transplants were investigated. Patients who underwent surgical dental treatment, such as extractions, biopsies, and scaling and root planning, to which different medications were administered were considered. Antibiotic prophylaxis was the most common medication administered, in addition to other medicines applied in the treatment of complications, such as post-operative bleeding. In conclusions, there is not enough scientific evidence to establish clear and universal recommendations for the management of solid organ transplant patients after oral surgery.